Effect of laser scanning speed on microstructure and mechanical properties of SLM porous Ti-5Al-5V-5Mo-3Cr-1Fe alloy - Yuan, Wei; Zhao, Xiaoli; Li, Shujun; Zhu, Yue (Frontiers in Materials, 2022)
In this study, porous Ti-55531(Fe) was fabricated by selective laser melting (SLM) with different laser scanning speeds. The microstructures, surface morphology, inner defects, porosity, microhardness and compressive behaviors were studied. The variation of lattice constant and hardness were analyzed. The results show that all the specimens have a density of ~1g/cm3, and a Vicker’s hardness with a range of 280~320 Hv0.1. The porosity of the SLM-produced materials is greater than the designed value (77%) and increases from 77.33% to 82.33% with the increase of laser scanning speed from 500 mm/s to 1500 mm/s. Continuous irregular columnar dendrites, a large number of gas-induced defects with small size between 20 and 60 μm and a deep molten pool form in the specimens fabricated with a laser scanning speed less than 1000 mm/s. Some defects, elongated voids and interrupted columnar dendrites are identified in the specimens fabricated with the laser scanning speed more than 1000 mm/s caused by the insufficient input energy. All specimens with different laser scanning speeds show the single β phase patterns. The compressive strength of the specimens with the laser scanning speed of 500 mm/s is maintained at 32 MPa and the compressive strength decreases with the increase of laser scanning speed. The specimens with a scanning speed of 500 mm/s present the best mechanical properties and surface quality.